Écritures, espaces et imaginaires cubains depuis l’exil - Michèle Guicharnaud-Tollis (Caravelle)
As a result of different emigration waves which have taken place since the Cuban revolution, a new imaginary space is appearing among Cuban exiles. Based on various texts (autobiographies, testimonies, poetry and fiction novel), we will study how the Cuban writers consider their own exile, then the use of different literary strategies which they implement to conceal or, on the contrary, to reveal the emergency of their new wandering and « transcultural » identity.